The Effect of Competence, Professionalism and Independence of Government Internal Supervisory Officials (APIP) on the Quality of Inspections at the Regional Supervision Inspectorate of the Regional Police of East Java: Pengaruh Kompetensi, Profesionalisme Dan Independensi aparat Pengawas Intern Pemerintah (APIP) Terhadap Kualitas Pemeriksaan di Inspektorat Pengawasan Daerah Polda Jawa Timur - Rahmat, Wijaya; Fitriyah, Hadiah (Universitas Muhammadiyah Sidoarjo, 2021)
This study aims to examine the effect of competence, professionalism and independence of the government's internal supervisory apparatus (APIP) on the quality of examinations at the East Java Regional Supervision Inspectorate. The research shows that there are various factors that can affect the quality of internal audits in their implementation. A common problem in this study is the existence of audit findings that were not detected by APIP as an internal auditor, but were found by an external auditor, the Supreme Audit Agency (BPK). This study uses a quantitative approach. The population of the study was 40 pariks / auditors at the Regional Supervision Inspectorate of the Regional Police of East Java. Sampling using simple random sampling method. The research data were analyzed using multiple regression method with the help of SPSS. The results of this study found that partially and simultaneously the variables of competence, independence and professionalism of auditors had a positive and significant effect on audit quality